UDK 537.322.15 ANALYSIS OF THE CURRENT STATUS OF THERMOELECTRIC MATERIALS AND TECHNOLOGY FOR OBTAINING AND MANUFACTURING HALF-ELEMENTS - Latipova, Muxayyo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. This article discusses in detail the materials that are of interest in the thermoelectric ratio. The most common members of the group in the periodic table of Mendeleev. The analysis of the current state of triple compound thermoelectric materials, which are the best materials for thermoelectric generators, as well as the methods and technology of production, the requirements for the technology of obtaining these materials, is carried out. Methods. Experimental studies were carried out to determine the optimal concentration of current carriers of the required sign, by the method of formation of a non-stoichiometric chemical composition, or by the method of introducing additional dopants. Results. To obtain a thermoelectric generator with high values ​​of efficiency, as our studies show, the method of fusion under pressure of an inert gas [6-10] is the most effective, which differs in that melting is carried out in a crucible with a shutter. At the same time, the issue of container reuse is being addressed. For the manufacture of half-elements, cutting of solids plays an important role, which affects the energy parameters and efficiency. Conclusion. The best and most effective way to obtain substances for the legs of a thermoelement is the method of fusion of the charge under the pressure of an inert gas. Thermoelectric semiconductor compounds obtained by this method have high values ​​of thermoelectric figure of merit Ζ, reaching up to 3.0 · 10-3 deg-1, which makes it possible to create thermopiles with the best efficiency. The use of an electric spark cutting machine makes it possible to obtain thermopiles with minimal defects and the best quality.